Ketoconazole- and Metyrapone-Induced Reductions on Urinary Steroid Metabolites Alter the Urinary Free Cortisol Immunoassay Reliability in Cushing Syndrome - Vega-Beyhart, Arturo; Laguna-Moreno, Javier; Díaz-Catalán, Daniela; Boswell, Laura; Mora, Mireia; Halperin, Irene; Casals, Gregori; Hanzu, Felicia A. (Frontiers in Endocrinology, 2022)
Introduction Twenty-four-hour urinary free cortisol (24h-UFC) is the most used test for follow-up decision-making in patients with Cushing syndrome (CS) under medical treatment. However, 24h-UFC determinations by immunoassays (IA) are commonly overestimated because of steroid metabolites' cross-reaction. It is still uncertain how Ketoconazole (KTZ) and Metyrapone (MTP)-induced changes on the urinary steroid metabolites can alter the 24h-UFC*IA determinations’ reliability. Methods: 24h-UFC was analyzed by IA and gas chromatography-mass spectrometry (GC-MS) in 193 samples (81 before treatment, 73 during KTZ and 39 during MTP) from 34 CS patients. In addition, urinary steroidome was analyzed by GC-MS on each patient before and during treatment. Results: Before treatment, 24h-UFC*IA determinations were overestimated by a factor of 1.75 (95% CI 1.60 - 1.94) compared to those by GC-MS. However, during KTZ treatment, 24h-UFC*IA results were similar (0.98:1) to those by GC-MS (95% CI, 0.83 – 1.20). In patients taking MTP, IA bias only decreased 0.55, resulting in persistence of an overestimation factor of 1.33:1 (95% CI, 1.09 -1.76). High method agreement between GC-MS and IA before treatment (R2 = 0.954), declined in patients under KTZ (R2 = 0.632) but not in MTP (R2 = 0.917). Upper limit normal (ULN) reductions in patients taking KTZ were 27% larger when using 24h-UFC*IA compared to 24h-UFC*GC-MS which resulted in higher falsely efficacy and misleading biochemical classification of 15% of patients. Urinary excretion changes of 22 urinary steroid metabolites explained 86% of the 24h-UFC*IA interference. Larger urinary excretion reductions of 6β-hydroxy-cortisol, 20α-dihydrocortisol and 18-Hydroxy-cortisol in patients with KTZ elucidated the higher 24h-UFC*IA bias decrement compared to MTP treated patients. Conclusion: KTZ and MTP alter the urinary excretion of IA cross-reactive steroid metabolites, thus decreasing the cross-reactive interference of 24h-UFC*IA determinations present before treatment. Consequently, this interference reduction in 24h-UFC*IA leads to loss of method agreement with GC-MS and high risk of overestimating the biochemical impact of KTZ and MTP in controlling CS because of poor reliability of reference ranges and ULN.